Gaps and blind spots limiting the efficacy of provaccine communication strategies: case studies of World Health Organization and South African government strategies - Pointer, Rebecca (Frontiers in Communication, 2025)
IntroductionVaccine communication strategies are essential for guiding effective provaccine communication to overcome vaccine hesitancy and address false information about vaccines. This research investigated whether the World Health Organization (WHO) and the South African government COVID-19 vaccine communication strategies helped define a suitable approach to provaccine communication and sufficiently upskilled vaccine communicators.MethodsA close textual reading was applied, with the contents being coded based on six elements of effective communication (power, desire, audience, framing, aesthetics and tools).ResultsThe study found that the strategies were not sufficiently rooted in communication theory, and mainly focused on appropriate dissemination tools. Both strategies strongly recommended audience listening and monitoring but neither provided detail on how audience analysis should influence communication approaches. The documents also provided many examples of possible messages but did not discuss framing as a strategic exercise. Further, although the documents mentioned audiences’ emotional states occasionally, they barely suggested methods for achieving positive affective states, including minimal mentions of aesthetics. Power was marginally mentioned in the WHO strategy but was not considered at all in the South African strategy.DiscussionBecause of the gaps in the strategy documents and the heavy focus on dissemination tools, communicators are not sufficiently equipped to develop persuasive campaigns to build solidarity and trust. Understanding power, the flow of desire and aesthetics are not just nice-to-have but are key persuasive elements in communications strategies, which must be incorporated into holistic vaccine communication strategies if we hope to address vaccine hesitancy and stem the flow of false vaccine information.